APPLICATION OF DRIP IRRIGATION SYSTEM FOR DIFFERENT MELON VARIETIES AND STUDY OF THE IMPACT ON YIELD (British Journal of Global Ecology and Sustainable Development, 2025)
This article presents information on the reasons for yield differences between 15 melon cultivars grown under drip irrigation. In the experiment, despite all varieties being irrigated with the same amount of water, yields varied by up to 6-7 times. This was due to differences in water use efficiency, root system development, and the formation of reproductive organs. The highest yields were observed in the Gulobi, Zar Gulobi, and Sakhovat varieties. These results demonstrate the need to study the water requirements of each variety and determine optimal irrigation rates. The findings support the rationale for optimizing drip irrigation based on varietal characteristics.